Chondrocytes Proliferation of Patients with Cartilage Lesions in Their Own Body for Use in Cartilage Tissue Engineering: Hypotheses on aNew Approach for the Proliferation of Autologous Chondrocytes: - Alizadeh, Akram; Abpeikar, Zahra; Soleimannejad, Mostafa (Galen Medical Journal, 2019)
Osteoarthritis is one of the most common chronic diseases, which have involved 250 million people around the world. One of the challenges in the field of cartilage tissue engineering is to provide an adequate source of chondrocytes to prevent changes in gene expression profile as a result of multiple passages.We hypothesized that by creating a low invasive lesion by scalpel or shear laser in the outer ear cartilage and stimulation of wound healing process, hyperplasia occurs and will provide an appropriate number of autologous chondrocytes for extraction and use in articular cartilage tissue engineering. Also, due to the effect of platelet-rich plasma and biomechanical forces in stimulating and accelerating of the repair process, these two factors can be used to achieve more desirable results.We describe a new approach to proliferate chondrocytes in the body. To evaluate this idea, various techniques of gene expression at the level of RNA or protein and animal experiments for histological studies can be used. Also, flowcytometry technique can be used to determine the cell viability and counting them.The use of autologous cell sources with minimal changes in gene expression profile can be promising in tissue engineering products. [GMJ.2019;8:e1483]